Developing and field testing the Neighbourhood Observational Tool for auditing urban community environments (CyNOTes) in the city of Limassol, Cyprus - Kleopa, Daphne; Panayiotou, Andrie G.; Kouta, Christiana; Middleton, Nicos (My University, 2023)
Systematic Social Observation provides supplementary information about the micro-scale neighborhood environment. This study explored the feasibility of neighborhood audits for the first time in the city of Limassol, Cyprus (population size, 2021 census: 258.900). The prevalence and variability of audited features were investigated using the 126-item CyNOTes inventory, organised along a typology of 17 domains. Two independent audits, with a repeat in two weeks, were performed across 30 randomly selected street segments, stratified in three groups of neighborhoods according to the educational attainment of residents. Associations with census indicators and survey data on SF-36 Quality of Life among residents aged 45–64 (N = 150) were explored. More adverse conditions were recorded in low educational attainment neighborhoods, with differences apparent in domains with generally high as well as low scores. Neighborhood scores correlated with census indicators of the built environment, while negative correlations where observed with sociodemographic indicators, such as population aged over 65 and non-Cypriot population, suggesting social inequities. In neighborhoods with more adverse features, lower physical and mental health-related quality of life were reported. Overall, the study documented environmental inequity. CyNOTes offers the potential for further development and scaling-up for public health research, policy, and advocacy.
Keywords: Neighborhood assessment; Neighborhood audit; Systematic social observation; Observer rating; Social gradient; Environmental equity